Sustaining Cooperatives through Governance, Resilience, and Innovation: A Systematic Literature Review and Future Research Agenda - Yoedani Yoedani; FITRINA LESTARI (Business Management, 2026)
Cooperatives are increasingly recognized as strategic institutions for inclusive and sustainable development, particularly in emerging economies where many community-based actors face limited access to finance, markets, technology, and institutional support. Yet, cooperative sustainability research remains fragmented across sectors, theories, methods, and outcomes. This systematic literature review synthesizes how governance, resilience, and innovation shape cooperative sustainability and future research directions. Drawing on Scopus-indexed literature from 2020 to 2026, this review followed a PRISMA-informed process. From 842 initial records, 475 reports were assessed after time-period filtering, and 82 studies were included. Thematic and framework-based synthesis organized the evidence into four themes: governance and institutional capacity, resilience and adaptive capacity, innovation and sustainable business models, and sustainability outcomes. The findings show that cooperative sustainability is not an automatic result of member ownership. It emerges from the alignment of participatory governance, institutional legitimacy, social capital, risk management, financial capacity, innovation readiness, and stakeholder coordination. Governance builds accountability, trust, participation, and clarity. Resilience helps cooperatives absorb shocks and protect livelihoods amid market, climate, disease, and financial uncertainty. Innovation supports transformation through digital capability, circular economy, certification, Islamic social finance, sustainable supply chains, and business model redesign. The review also identifies tensions related to elite capture, weak accountability, facilitation dependency, gender exclusion, digital inequality, and inconsistent measurement. This review reframes cooperative sustainability as a multidimensional strategic process, not merely organizational survival. It proposes an integrated governance–resilience–innovation perspective and calls for longitudinal, comparative, multi-level, and mixed-method research to explain when, how, and under what conditions cooperatives create sustainable value.